Anti-apoptotic mechanisms of HIV: lessons and novel approaches to curing HIV - Cummins, Nathan W. (Springer Basel, 2012)
Past efforts at curing infection with the human immunodeficiency virus (HIV) have been blocked by the resistance of some infected cells to viral cytopathic effects and the associated development of a latent viral reservoir. Furthermore, current efforts to clear the viral reservoir by means of reactivating latent virus are hampered by the lack of cell death in the newly productively infected cells. The purpose of this review is to describe the many anti-apoptotic mechanisms of HIV, as well as the current limitations in the field. Only by understanding how infected cells avoid HIV-induced cell death can an effective strategy to kill infected cells be developed.